1997
DOI: 10.1007/bf02888293
|View full text |Cite
|
Sign up to set email alerts
|

A new drug delivery system—Ciprofloxacine/tricalcium phosphate delivery capsule (CTDC) and itsIn Vitro drug release pattern

Abstract: A new drug delivery system (DDS), ciprofloxacine/tricalcium phosphate delivery capsule (CTDC) was developed by loading a broad-spectrum antibiotic ciprofloxacine into the central cylindrical cavity of tricalcium phosphate capsule. The new system showed good biocompatibility and could degrade gradually in our preliminary studies. In vitro study showed that CTDC could maintain high-level and long-term release of ciprofloxacine and that ultrasonic irradiation within the range of physical therapy could increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Various studies have demonstrated that nitrogenous bisphosphonates such as zolendronate can inhibit abrasion-induced osteolysis and lead to increased peri-implant bone density [7,8]. Alendronate belongs to the group of bisphosphonates and is already being applied in medical therapy and prophylactically for osteoporosis [9]. Bone structure is made denser by the consistent delivery of alendronate, making the bone less fracture prone [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have demonstrated that nitrogenous bisphosphonates such as zolendronate can inhibit abrasion-induced osteolysis and lead to increased peri-implant bone density [7,8]. Alendronate belongs to the group of bisphosphonates and is already being applied in medical therapy and prophylactically for osteoporosis [9]. Bone structure is made denser by the consistent delivery of alendronate, making the bone less fracture prone [10,11].…”
Section: Introductionmentioning
confidence: 99%